Español - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1985)
From the calcareous mountains of the North Eastern zone, belonging to the "Betica" corological province, (Subbetico section) it stands out becouse of its height: the Macizo de la Sagra. With our refferences is enlarged the area of localization inside the Granada province, and is ratified the presence of sorne of the taxa which are mentioned.